To determine if -7 is greater than -11 when f = -11, we substitute -11 for f in the inequality:
-7 > -11
-7 is indeed greater than -11, so the statement is true when f = -11.
However, when f = -10, the inequality becomes:
-7 > -11
-7 is still greater than -11, so the statement is true when f = -10 as well.
When f = -2, the inequality becomes:
-7 > -11
Again, -7 is greater than -11, so the statement is true when f = -2.
Finally, when f = -4, the inequality becomes:
-7 > -11
Once again, -7 is greater than -11, so the statement is true when f = -4 as well.
In conclusion, for all the given values of f, the inequality -7 > -11 holds true.
f -7 > - 11 of f = -11 f = -10 f = -2 f = -4
1 answer